Implementation of The Independent Learning Curriculum in Cirebon District - Arif Rohman Hakim; Maulina Nabila (Syntax Corporation Indonesia, 2022)
Freedom to learn is an idea launched by the minister of education and culture, to produce superior human resources by prioritizing character education. This study aims to determine the implementation of independent learning policies in education in Indonesia. This study uses a literature review research method, while data collection techniques are carried out by exploring journals and other information relevant to the study. The results showed that the independent learning program launched by the Minister of Education and Culture Nadiem Makarim was to improve the education system in Indonesia. The independent learning program is relevant to the goal of national education, namely to form a young generation who is not only intellectually intelligent but also has good character traits such as responsibility, discipline, honesty, has the ability to think critically and analytically and become independent humans so that they are able to express their opinions without feeling scared and depressed. Based on the explanation that has been given to the implementation of the Free Learning Policy promoted by the Minister of Education of Indonesia Nadiem Makarim in Cirebon Regency, it is hoped that it can increase the education ranking of Cirebon which previously occupied the 25th position in West Java, to be able to rise to the top.